Triaxial strength behavior of carbide sludge (CS)–ground-granulated blastfurnace slag (GGBS)-treated clay slurry - Li, Wentao (2022)
Dredging activities generate a huge amount of dredged clay slurry, and the treatment of it has been a challenge. Carbide sludge (CS)-activated ground-granulated blastfurnace slag (GGBS) can effectively stabilize clay slurry. However, in previous studies, the mechanical performance of CS–GGBS-treated slurry was only investigated through unconfined compressive strength (UCS) test, not triaxial shear strength test. Hence, in this study, the consolidated undrained (CU) triaxial test was conducted to investigate the triaxial strength behavior of CS–GGBS-treated slurry with 100% water content. The binder content was 60 kg/m3, and three CS:GGBS ratios of 1:9, 2:8, and 3:7 were used. For each treated slurry, six different pre-shear consolidation pressures ranging from 30 to 300 kPa were used. Results reveal that CS–GGBS-treated slurry has a bilinear failure envelop. When the pre-shear consolidation pressure is smaller than the yield stress, treated slurry has an effective cohesion of ~ 0.5UCS with an effective friction angle close to zero. However, when the pre-shear consolidation pressure exceeds the yield stress, the treated slurry only has a low effective cohesion of 0.13–0.26UCS, but a high effective friction angle of 31°-38°, higher than that of the untreated clay, i.e., 26°. This CU behavior of treated slurry can be explained by the soil-cementation structure upon shearing. When the pre-shear consolidation pressure is lower than the yield stress, the soil-cementation structure is nearly intact, which dominates the strength of treated slurry; however, when under high consolidation pressure, most cementation bonds break, and hence, the shear strength is attributed to the friction among soil particles and cohesion provided by residual cementation bonds. The influence of consolidation pressure on the treated slurry is further validated by isotropic consolidation results.